A photovoltaic module

By introducing a closed-cell structure of 0.5-20μm into the bonding layer of the photovoltaic module, the problem of easily cracking of the battery cells is solved, the impact resistance and power generation efficiency of the module are improved, and the lightweight is achieved.

CN114566559BActive Publication Date: 2025-04-18HANGZHOU FIRST APPLIED MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210337581.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-31
Publication Date
2025-04-18
Estimated Expiration
2042-03-31

AI Technical Summary

Technical Problem

In photovoltaic modules, the cell chips are prone to cracks due to stress, which reduces the power generation efficiency and causes damage to the module. This problem is more likely to occur when thin-filled battery cells are used.

Method used

The closed-cell structure is introduced into the bonding layer of the photovoltaic module, with the pore size of the closed-cell is 0.5-20 μm and the cell rate is 0.5-40%, to improve the impact resistance and lightweight properties of the module.

Benefits of technology

By introducing a closed-cell structure, the impact pressure of the battery cell during use is reduced, the impact resistance and power generation efficiency of the photovoltaic module are improved, and the components are lightweighted.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114566559B_ABST
    Figure CN114566559B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of photovoltaic technology. The present invention discloses a photovoltaic module comprising a front substrate, an adhesive layer, a cell sheet, an adhesive layer and a back substrate in sequence. At least one of the adhesive layers has closed pores, which do not protrude from the surface of the adhesive layer, and the pore size of the closed pores is 0.5-20 μm. The porosity of the adhesive layer is 0.5-40%. The present invention is applied to photovoltaic power generation and has good impact resistance, high power generation efficiency and good service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photovoltaics, and in particular relates to a photovoltaic component. Background Art

[0002] As energy crisis and environmental problems become increasingly serious, sustainable clean energy has attracted much attention. Photovoltaic technology, as the leader among them, has always been valued by my country. Photovoltaic technology refers to the technology that can directly convert solar light energy into electrical energy. The power generation process is pollution-free and in line with the concept of sustainable development.

[0003] Photovoltaic modules are the main components of photovoltaic technology and also the most important part. Photovoltaic modules are mainly composed of front panels, cells, back panels and packaging films. Their function is to convert sunlight into electrical energy for people to use or store. The cells are the ones that play the role of conversion in photovoltaic modules, but the main application environment of photovoltaic modules is outdoors, and the cells are very likely to fail or break due to environmental factors. Therefore, the cells must be packaged into photovoltaic modules to protect the cells.

[0004] However, the inventors of this application found that the above technology has at least the following technical problems in the process of implementing the technical solution in the embodiment of this application:

[0005] In the prior art, in order to ensure higher power generation efficiency and lower production costs, thin-film high-efficiency solar cells are receiving more and more attention, and higher and higher requirements are placed on photovoltaic modules.

[0006] During the use of photovoltaic modules, the cells are prone to hidden cracks due to stress, which reduces the power generation efficiency of the photovoltaic modules and even causes damage to the photovoltaic modules; especially for thin-film cells, hidden cracks and other problems are more likely to occur. Summary of the invention

[0007] The embodiment of the present application provides a photovoltaic module, which solves the problem of hidden cracks easily occurring in the cells of the photovoltaic module and ensures the power generation efficiency of the photovoltaic module.

[0008] An embodiment of the present application provides a photovoltaic module, which includes a front substrate, an adhesive layer, a battery cell, an adhesive layer and a back substrate in sequence, at least one of the adhesive layers has closed pores, and the closed pores do not protrude from the surface of the adhesive layer; the pore size of the closed pores is 0.5-20μm, preferably 0.5-10μm; the porosity of the adhesive layer is 0.5-40%; preferably 1-10%.

[0009] Preferably, the Shore hardness of the bonding layer at 23°C is less than or equal to 75HA, the storage modulus of the bonding layer at 23°C is less than or equal to 15MPa, and the volume resistivity of the bonding layer is greater than or equal to 10 14 Ω·m.

[0010] Preferably, the adhesive layer includes a transparent adhesive layer and a non-transparent adhesive layer, and the raw material of the adhesive layer includes a base resin; the adhesive layer arranged between the front substrate and the battery cell is the first adhesive layer, and the adhesive layer arranged between the back substrate and the battery cell is the second adhesive layer; the first adhesive layer is a transparent adhesive layer, and the second adhesive layer is a transparent foam film adhesive layer or a non-transparent adhesive layer.

[0011] Preferably, in the transparent adhesive layer, the pore size of the closed pores is 1-10 μm, and the volume resistivity is greater than or equal to 10 16 Ω·m; the density of the transparent adhesive layer is less than the density of the base resin, the Shore hardness of the transparent adhesive layer is less than or equal to 65HA, and the storage modulus of the transparent adhesive layer at 23° C. is less than or equal to 6MPa.

[0012] Preferably, in the non-transparent adhesive layer, the pore size of the closed pores is 5-20 μm, and the volume resistivity is greater than or equal to 10 14 Ω·m; the Shore hardness of the non-transparent adhesive layer is less than or equal to 70HA, and the storage modulus of the non-transparent adhesive layer at 23°C is less than or equal to 13MPa.

[0013] Preferably, when the porosity of the non-transparent adhesive layer is less than or equal to 6%, the density of the non-transparent adhesive layer is greater than the density of the matrix resin; when the porosity of the non-transparent adhesive layer is greater than 6%, the density of the non-transparent adhesive layer is less than the density of the matrix resin.

[0014] Preferably, the density of the transparent adhesive layer is less than that of the non-transparent adhesive layer, the Shore hardness of the transparent adhesive layer is less than that of the non-transparent adhesive layer, the storage modulus of the transparent adhesive layer at 23°C is less than that of the non-transparent adhesive layer at 23°C, the transmittance of the transparent adhesive layer is greater than that of the non-transparent adhesive layer, and the reflectivity of the transparent adhesive layer is less than that of the non-transparent adhesive layer.

[0015] Preferably, the adhesive layer is selected from a foam film, and the foam film is subjected to a micro-cross-linking treatment.

[0016] Preferably, the micro-crosslinking treatment includes at least one of ultraviolet light curing micro-crosslinking, thermal curing micro-crosslinking, radiation curing micro-crosslinking or microwave curing micro-crosslinking.

[0017] Preferably, the foamed rubber film comprises a cellular layer having pores, and the raw materials of the cellular layer include a base resin, a foaming agent, a functional auxiliary agent and a filler.

[0018] Preferably, the matrix resin includes at least one of EVA resin, POE resin, PE resin, PVB resin, EPDM resin or PU resin.

[0019] Preferably, the foaming agent includes at least one of a physical foaming agent or a chemical foaming agent.

[0020] Preferably, the physical foaming agent includes at least one of CO2, N2 or a microsphere foaming agent.

[0021] Preferably, the chemical foaming agent includes at least one of foaming agent TSH, foaming agent OBSH, foaming agent AC, ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, calcium bicarbonate or magnesium bicarbonate.

[0022] Preferably, the functional auxiliary agent includes at least one of a crosslinking agent, a co-crosslinking agent, a coupling agent, a heat stabilizer, a light stabilizer or a UV absorber.

[0023] Preferably, the filler includes at least one of carbon black, titanium dioxide, barium sulfate, bentonite, white carbon, wollastonite, whisker silicon, talc, magnesium hydroxide, magnesium oxide, aluminum hydroxide or aluminum oxide.

[0024] Preferably, in the cellular layer of the foam film, the Shore hardness of the cellular layer is less than or equal to 75HA, the storage modulus of the cellular layer at 23°C is less than or equal to 15MPa, the porosity is 1-80%, the pore size is 1-40μm, and the volume resistivity is greater than or equal to 10 14 Ω·m.

[0025] Preferably, the photovoltaic module is prepared by laminating a front substrate, a foam film, a battery cell, a foam film and a back substrate in sequence and then laminating at 90° C.-200° C.

[0026] In summary, the technical solution provided by the embodiments of the present application has at least the following beneficial effects:

[0027] 1. In the embodiment of the present application, at least one adhesive layer has closed pores, which can reduce the impact received by the solar cell when the photovoltaic module is used, and improve the impact resistance of the photovoltaic module;

[0028] 2. In the embodiments of the present application, at least one adhesive layer has closed pores, which solves the problem of heavy weight of photovoltaic modules and is conducive to lightweighting of photovoltaic modules. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A schematic diagram of a cross-sectional structure of a photovoltaic module in this application;

[0030] Figure 2 is a schematic diagram of the cross-sectional structure of another photovoltaic module in this application;

[0031] Figure 3 is a schematic diagram of the cross-sectional structure of another photovoltaic module in this application;

[0032] Figure 4 This is a schematic diagram of the cross-sectional structure of the pore layer in one implementation of the present application;

[0033] Figure 5 Schematic diagram of the cross-sectional structure of a conventional adhesive film;

[0034] Figure 6 Schematic diagram of the cross-sectional structure of conventional photovoltaic modules in Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0035] In order to make those skilled in the art better understand the scheme of the present invention, the technical scheme in the specific implementation mode of the present application will be clearly and completely described below in conjunction with the drawings in the implementation mode of the present application. It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict. The present application will be described in detail below in conjunction with the embodiments.

[0036] In order to solve the problem of hidden cracks in the cell during the lamination process of the photovoltaic module, the embodiment of the present application uses a foam film 16 during the packaging process of the photovoltaic module 100 to form an adhesive layer with closed pores 121, thereby reducing the pressure on the cell 13 when the photovoltaic module 100 is in use and preventing the cell 13 from hidden cracks.

[0037] like Figure 1 As shown, an embodiment of the present application provides a photovoltaic module 100, which includes a front substrate 11, an adhesive layer, a battery cell 13, an adhesive layer and a back substrate 15 in sequence. The front substrate 11 is arranged on the light-facing side of the battery cell 13 to protect the battery cell 13, and the back substrate 15 is arranged on the backlight side of the battery cell 13 to protect the battery cell 13. The adhesive layer includes a first adhesive layer 12 and a second adhesive layer 14. The first adhesive layer 12 is arranged between the front substrate 11 and the battery cell 13 to bond the front substrate 11 and the battery cell 13 together, and the second adhesive layer 14 is arranged between the back substrate 15 and the battery cell 13 to bond the back substrate 15 and the battery cell 13 together. At least one of the adhesive layers in the photovoltaic module 100 has closed pores 121, and the closed pores 121 do not protrude from the surface of the adhesive layer. Specifically, the closed pores 121 (such as Figure 1 As shown), the closed pores 121 may be provided only in the second adhesive layer 14 (as shown Figure 2 As shown), closed cells 121 may also be provided in both the first adhesive layer 12 and the second adhesive layer 14 (as shown Figure 3As shown). The pore size of the closed pores is 0.5-20 μm, preferably 0.5-10 μm; the porosity of the adhesive layer (referring to the percentage of the volume of the closed pores in the adhesive layer to the volume of the adhesive layer) is 0.5-40%, preferably 1-10%. At least one of the first adhesive layer 12 or the second adhesive layer 14 of the photovoltaic module 100 has closed pores 121, which improves the impact resistance of the photovoltaic module 100, reduces the impact on the battery cell 13 when the photovoltaic module 100 is in use, and increases the service life of the photovoltaic module 100. The closed pores 121 in the adhesive layer can prevent water vapor from entering the interior of the photovoltaic module 100 through the closed pores 121 when the photovoltaic module 100 is in use, thereby extending the service life of the photovoltaic module 100. When the size of the closed pore 121 is smaller than a certain size, the existence of the closed pore 121 will not affect the strength of the bonding layer. On the contrary, when the crack expands under stress conditions, the closed pore 121 can passivate the crack tip and prevent the crack from further expanding. Not only will it not cause the loss of mechanical properties of the closed pore 121, but it can also improve the mechanical properties of the closed pore 121.

[0038] As an implementation method, the Shore hardness of the bonding layer is less than or equal to 75HA, the storage modulus is less than or equal to 15MPa at 23°C, and the volume resistivity is greater than or equal to 10 14 Ω·m. The introduction of closed pores 121 into the bonding layer of the photovoltaic module 100 effectively reduces the Shore hardness and storage modulus of the bonding layer, so that the bonding layer has better buffering performance, protects the battery cell 13 when the photovoltaic module 100 is impacted, and improves the impact resistance of the photovoltaic module 100. At the same time, after the closed pores 121 are introduced into the bonding layer, the volume resistivity will be correspondingly improved, which can effectively improve the volume resistance of the bonding layer, meet the use requirements of high resistance of the bonding layer, reduce the leakage current when the photovoltaic module 100 is used, and improve the power generation efficiency and service life of the photovoltaic module 100.

[0039] As an implementation method, at least one of the first adhesive layer 12 or the second adhesive layer 14 in the embodiment of the present application is made of a foam film 16, and the foam film 16 is subjected to a micro-crosslinking treatment. Preferably, the micro-crosslinking treatment includes at least one of ultraviolet light curing micro-crosslinking, heat curing micro-crosslinking, radiation curing micro-crosslinking or microwave curing micro-crosslinking. In the embodiment of the present application, at least one of the first adhesive layer 12 or the second adhesive layer 14 is made of a foam film 16, which can effectively reduce the pressure generated during packaging when the photovoltaic module 100 is packaged, and prevent the battery cell 13 from cracking due to pressure. The pores 161a in the pore layer 161 in the foam film 16 can absorb the instantaneous pressure generated by the packaging when the photovoltaic module 100 is packaged, thereby reducing the instantaneous pressure on the battery cell 13, protecting the battery cell 13 from cracking, and improving the packaging quality of the photovoltaic module 100. In the embodiment of the present application, the foamed foam film 16 is subjected to a micro-crosslinking treatment, which is beneficial to improving the strength of the foam film 16, improving the shape retention performance of the pores 161a, and making the foam film 16 have a lower Shore hardness and higher impact resistance. The pores 161a in the foam film 16 can better maintain their shape when the photovoltaic module 100 is laminated and packaged, thereby improving the protective effect of the foam film 16 on the battery cell 13. The adhesive layer formed after the photovoltaic module 100 is packaged can retain more closed cells 121, thereby improving the impact resistance of the photovoltaic module 100 after packaging. The closed cells 121 in the adhesive layer are obtained from the pores 161a in the foam film 16 after lamination.

[0040] As an implementation method, the foam film 16 selected in the present application includes a foam layer 161 having pores 161a (such as Figure 4 As shown), the cellular layer 161 is made by foaming the cellular layer composition. The cellular layer composition includes a base resin, a foaming agent and a functional auxiliary agent. The cellular layer 161 is mainly made by adding a functional auxiliary agent and a foaming agent to a base resin and then undergoing a foaming treatment. Through the design of the foaming system and the optimization of the foaming process, the cellular layer 161 can obtain ultra-micropores with nanometer size. When the size of the pores 161a in the cellular layer 161 is less than a certain size, the presence of the pores 161a does not reduce the strength of the cellular layer 161. On the contrary, when the crack expands under stress conditions, the micropores can passivate the crack tip, prevent the crack from further expanding, and improve the mechanical properties of the cellular layer 161. In the embodiment of the present application, at least one of the first bonding layer 12 or the second bonding layer 14 is made of a foamed adhesive film 16, and the closed cells 121 are obtained by laminating the pores 161a. Therefore, the embodiment of the present application can control the components of the cellular layer composition according to the actual use requirements of the bonding layer in the photovoltaic module 100, obtain the required foam film 16, and obtain the bonding layer that meets the use requirements after lamination and packaging. In addition to meeting the requirement of having a cellular layer, the foam film can also be provided with a corresponding functional layer according to actual needs.

[0041] As an implementation method, the matrix resin in the cellular layer composition includes at least one of EVA resin, POE resin, PE resin, PVB resin, EPDM resin or PU resin. The main component of the cellular layer composition is the matrix resin. Different matrix resins can give the cellular layer 161 different properties. The cellular layer 161 is appropriately adjusted according to the production requirements of the photovoltaic module 100. The cellular layer 161 made of EVA resin in the matrix resin has good buffering and shock resistance, does not absorb water, is moisture-proof and has good water resistance. EVA resin has superior performance in terms of adhesion, durability and optical properties. POE resin has the dual characteristics of plastic and rubber, and has excellent mechanical properties and low temperature properties. The film made of POE resin has excellent water vapor barrier capacity and ion barrier capacity, and the water vapor permeability is only about 1 / 8 of EVA. It performs outstandingly in an environment with high humidity, and its molecular chain structure is stable. The aging process will not decompose to produce acidic substances, and it has excellent anti-aging properties. After foaming, POE resin has high tensile strength and tear strength, good elasticity and wear resistance, and can well protect the battery cell 13. PE resin has excellent low temperature resistance, good chemical stability, and can withstand most acid and alkali erosion. After foaming, PE resin is light in weight, has good resilience, can adjust the hardness and thickness at will, and has excellent buffering performance, and does not lose its original performance after strong impact. PVB resin has excellent transparency, good flexibility, low glass transition temperature, high tensile strength and impact strength. EPDM resin has excellent aging resistance and corrosion resistance, strong acid and alkali resistance, excellent insulation performance and a wide temperature application range. After foaming, EPDM resin combines the softness and good resilience of EPDM resin itself, so that the foam layer 161 has better buffering performance. The foam layer 161 made of PU resin has good stability, chemical resistance, resilience and mechanical properties, has smaller compression deformation, can absorb instantaneous pressure well, and reduces the risk of battery cell fragmentation. According to different usage requirements or production needs of the photovoltaic module 100 , the type of the matrix resin in the foam layer composition can be appropriately adjusted to meet the production and usage requirements of the photovoltaic module 100 .

[0042] As an implementation method, the foaming agent in the cellular layer composition includes at least one of a physical foaming agent or a chemical foaming agent. The physical foaming agent includes at least one of CO2, N2 or a microsphere foaming agent. The chemical foaming agent includes at least one of a foaming agent TSH, a foaming agent OBSH, a foaming agent AC, ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, calcium bicarbonate or magnesium bicarbonate. The foaming method used in the cellular layer 161 includes at least one of physical foaming or chemical foaming. The foaming agent for physical foaming is at least one of CO2, N2 or a microsphere foaming agent, and also includes any other substance whose volume can increase after the external conditions change. The physical foaming agent mainly achieves the purpose of foaming by changing the physical form of the substance. Among the physical foaming agents, the foaming agent CO2 and the foaming agent N2 include conventional liquid CO2 and liquid N2, and also include CO2 and N2 in a supercritical state. Liquids whose temperature and pressure are above the critical point are called supercritical fluids. The viscosity and diffusion coefficient of supercritical fluids are closer to gases, while the density and solvation capacity are closer to liquids. The properties such as density, diffusion coefficient, and solvation capacity are very sensitive to changes in temperature and pressure. Supercritical fluids can be used to prepare a pore layer 161 with smaller pore size, higher pore number, and better comprehensive performance. In the foaming process, the supercritical fluid is injected into the device to form a single-phase mixed sol after the gas, matrix resin, and functional additives are fully and evenly mixed. The sol is then introduced into the mold cavity or extrusion die to produce a large pressure drop in the sol, so that the gas is precipitated to form a large number of bubble nuclei. In the subsequent cooling and molding process, the bubble nuclei inside the sol continue to grow and form, and finally a microporous foamed pore layer 161 is obtained. Since the viscosity of the supercritical fluid is close to that of the gas, and the diffusion capacity is much greater than that of the liquid, the pores 161a of the supercritical foaming are more delicate, more evenly distributed, and the particle size is controllable, thereby making the pore layer 161 have better thermal stability and toughness. The critical pressure and temperature of the supercritical fluid are relatively mild and easy to achieve, and the polymer has good solubility, strong diffusion ability and easy control, which can well control the foaming progress of the cellular layer 161. In addition, the supercritical fluid can also increase the free volume of the polymer, improve the mobility of the molecular chain, reduce the glass transition temperature of the polymer and the viscosity of the system, and has a significant plasticizing effect, which can effectively improve the processing performance of the matrix resin. After molding, CO2 or N2 exists in the form of gas, which has no adverse effect on the cellular layer 161. The microsphere foaming agent is composed of a polymer shell and an unstable core, and has an appearance of white powder. It begins to expand at the softening point of the shell and the thermoplastic shell softens at an appropriate temperature. At the same time, the core-shell structure is not destroyed, and the gas inside the shell begins to expand, and the volume can rapidly expand to dozens of times its own volume, thereby achieving the effect of foaming. The microsphere foaming agent is simple to use, and can be added to the formula, mixed and stirred evenly, without the need to adjust the original process.The shell of the microsphere foaming agent has good elasticity and can withstand greater pressure. After heating and expansion, the foaming agent itself does not break and can maintain its own good performance. The pores 161a formed after foaming can effectively improve the mechanical properties of the pore layer 161, prevent the battery cell 13 from being subjected to excessive instantaneous pressure and cracking when the photovoltaic module 100 is packaged, and improve the buffering performance of the photovoltaic module 100 after packaging. In addition, the microsphere foaming agent can also well control the density and pore size of the pores 161a of the pore layer 161, which is helpful for the control and optimization of the foaming process. Chemical foaming is different from physical foaming. During the foaming process, the foaming agent usually decomposes in whole or in part and produces foaming byproducts that are at least partially gaseous. Therefore, when selecting a foaming agent, it is necessary to select a suitable foaming agent for foaming according to the base resin and the scope of use. The foaming agent TSH is a low-temperature foaming agent with a wide range of applications. It can produce a fine closed-cell structure in the pore layer 161, and the product has a small shrinkage rate and high tear strength. The foaming agent OBSH is environmentally friendly and has a wide range of applications. It is often used for foaming rubber products. The foaming temperature is low and the product is pollution-free. The foaming agent AC is easily decomposed into nitrogen, carbon monoxide and carbon dioxide when heated. The foaming layer 161 formed by foaming has good elasticity and high strength, and the pores 161a formed have uniform pore size. Ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, calcium bicarbonate and magnesium bicarbonate are all carbonate foaming agents with low decomposition temperatures, and have the advantages of safety, endothermic decomposition, and good nucleation effect. When the foaming agent is foaming agent AC or foaming agent OBSH, adding an appropriate amount of foaming activator can increase the foaming efficiency and foaming amount. According to the use and production requirements of the photovoltaic module 100 produced, the foaming process design of the foam layer 161 is carried out, and a suitable foaming agent is selected to meet the different foaming requirements of the foam layer 161 in the foam film 16 used by different photovoltaic modules 100, so that the photovoltaic module 100 has good buffering performance.

[0043] As an implementation method, the functional additives in the cellular layer composition include at least one of a crosslinking agent, a co-crosslinking agent, a coupling agent, a heat stabilizer, a light stabilizer or a UV absorber. In order to ensure the performance of the cellular layer 161, it is necessary to add appropriate functional additives to the cellular layer 161 according to the use requirements. According to the selected matrix resin, a crosslinking agent, a co-crosslinking agent, and a coupling agent are selected to help the matrix resin form a film, form a network structure, improve the strength and elasticity of the cellular layer 161, and the bonding layer obtained after lamination has good mechanical properties. Heat stabilizers, light stabilizers, and UV absorbers are used to improve the stability of the cellular layer 161, strengthen the weather resistance of the bonding layer after the photovoltaic module 100 is encapsulated, and improve the environmental adaptability of the photovoltaic module 100.

[0044] As an implementation method, the cellular layer composition also includes a filler. The filler includes at least one of carbon black, titanium dioxide, barium sulfate, bentonite, white carbon, wollastonite, whisker silicon, talc, magnesium hydroxide, magnesium oxide, aluminum hydroxide and aluminum oxide. The embodiment of the present application is applied to the field of photovoltaic technology. Regardless of the light-facing side or the backlight side, the light absorption rate of the film should be as small as possible. Therefore, when the cellular layer composition selects fillers, white fillers are mainly used to achieve higher light utilization. At the same time, the filler added in the cellular layer 161 can be used as a foaming nucleating agent during foaming, and the mechanical properties of the cellular layer 161 can be enhanced after foaming molding. It can also improve the fluidity during film formation to ensure that the cellular layer 161 is uniformly filmed. The foaming film 16 is used to bond the battery cell 13 and the substrate of the photovoltaic module 100. According to the type of photovoltaic module 100 used, the filler added in the cellular layer 161 needs to be properly controlled. After the photovoltaic module 100 is packaged, the filler in the formed adhesive layer can also increase the light reflectivity, the utilization rate of light by the photovoltaic module 100, and improve the power generation efficiency of the photovoltaic module 100.

[0045] As an implementation method, in the pore layer 161 of the foam film 16, the porosity is 1 to 80%, preferably 1 to 20%; the density of the pores 161a is 10 6 -10 8 pcs / m 2 , pore size is 1-40μm, volume resistivity is greater than or equal to 10 14 Ω·m. In the embodiment of the present application, at least one of the adhesive layers is made of a foam film 16, so the performance of the foam film 16 directly affects the performance of the adhesive layer in the photovoltaic module 100. Controlling the performance parameters of the foam film 16 can effectively control the performance of the adhesive layer after the photovoltaic module 100 is laminated and packaged, so that the closed cells 121 of the adhesive layer have appropriate density and pore size, ensuring that the adhesive layer has good impact resistance and high volume resistivity.

[0046] As an implementation method, the foam film 16 includes a transparent foam film and a non-transparent foam film. The first adhesive layer 12 is made of a transparent foam film, and the second adhesive layer 14 is made of a transparent foam film or a non-transparent foam film. In the photovoltaic module, since the front side needs to be exposed to light, the first adhesive layer is made of a transparent packaging film, and the transparent packaging film forms a transparent adhesive layer after lamination. Depending on the type of the module, the second packaging film is made of a transparent packaging film or a non-transparent packaging film. The transparent foam film forms a transparent adhesive layer after lamination, and the non-transparent foam film forms a non-transparent foam film after lamination. Specifically, when the photovoltaic module 100 is a single-sided module, the first adhesive layer 12 uses a transparent foam film to ensure that the light-facing surface of the photovoltaic module 100 has good light transmittance, increase the light transmittance, and make the photovoltaic module 100 have good power generation efficiency, and the second adhesive layer 14 uses a non-transparent foam film to increase the reflectivity of the backlight surface of the photovoltaic module 100 and improve the light utilization rate of the photovoltaic module 100. When the photovoltaic module 100 is a double-sided module, both the light-facing surface and the backlight surface of the photovoltaic module 100 need a high light transmittance to ensure the light transmittance, so the first adhesive layer 12 and the second adhesive layer 14 are both transparent foam films.

[0047] As an implementation method, in the pore layer 161 of the transparent foam film, the density of the pores 161a is 10 6 -10 8 pcs / m 2 The pore size of pore 161a is 1-10 μm, and the volume resistivity is greater than or equal to 10 16 Ω·m. The density of the cellular layer 161 in the transparent foam film is less than the density of the base resin, the Shore hardness of the cellular layer 161 in the transparent foam film is less than or equal to 65HA, and the storage modulus at 23°C is less than or equal to 6MPa. The cellular layer 161 of the transparent packaging film is prepared by adding little or no filler to the base resin. Since little or no filler is added, the density of the cellular layer 161 of the transparent foam film 16 is relatively small.

[0048] As an implementation method, in the pore layer 161 of the non-transparent foam film, the density of the pores 161a is 10 6 -10 8 pcs / m 2 The pore size of pore 161a is 5-20 μm, and the volume resistivity is greater than or equal to 10 14Ω·m. The Shore hardness of the cellular layer 161 is less than or equal to 70HA, and the storage modulus at 23°C is less than or equal to 13MPa. In the prior art, in photovoltaic modules, especially for single-sided modules, in order to increase the utilization rate of sunlight, a non-transparent encapsulation film is usually used on the back of the photovoltaic module to enhance the light reflectivity of the back of the photovoltaic module, improve the utilization rate of sunlight, and enhance the power generation efficiency of the photovoltaic module. Generally speaking, the opaque encapsulation film is made into a white encapsulation film. More fillers are added to the non-transparent encapsulation film to give the encapsulation film a color. Although more fillers are added, due to the difference in the actual added filler content and the influence of the foaming ratio, the density of the non-transparent film is greater than that of the matrix resin, and there is also a case where the density of the non-transparent film is less than or equal to that of the matrix resin. Since the non-transparent foam film has more fillers added, it has a relatively high Shore hardness and a larger storage modulus relative to the transparent foam film. Due to the addition of more fillers, the non-transparent foam film has a lower light transmittance and a higher light reflectivity. In the present application, the density and pore size of the pores 161a of the cellular layer 161 in the transparent foam film and the non-transparent foam film are basically the same. When within the above range, the foaming condition of the foam film 16 is good and can meet the actual use requirements. When the photovoltaic module 100 is laminated and packaged, a large instantaneous pressure is generated. The embodiment of the present application uses the foam film 16 to relieve the absorption of the instantaneous pressure to prevent the battery cell 13 from cracking. The cellular layer 161 in the foam film 16 is the main part of relieving the absorption of the instantaneous pressure. Therefore, it is necessary to effectively design the cellular layer 161. The foaming process of the cellular layer 161 is designed so that the cellular layer 161 has a specific density and pore size of pores 161a. Through the design of the foaming system and the optimization of the foaming process, the cellular layer 161 can obtain ultra-micropores with nanometer size. The introduction of pores 161a in the cellular layer 161 can also effectively increase the volume resistivity of the cellular layer 161, ensuring the safety of the photovoltaic module 100 after packaging. The pores 161a in the cellular layer 161 have a diameter within the range of 5-20 μm, which can ensure the strength of the cellular layer 161, reduce the difficulty of foaming, improve the uniformity of foaming, and also ensure that more closed cells 121 can be retained in the bonding layer of the photovoltaic module 100 after lamination. At the same time, since the cellular layer 161 of the transparent foam film has less or no filler added, it has a larger volume resistivity; the cellular layer 161 of the non-transparent foam film has more fillers added, and has a smaller volume resistivity than the transparent foam film.

[0049] As an implementation method, the density of the cellular layer 161 in the transparent foam film is less than the density of the cellular layer 161 in the non-transparent foam film, the Shore hardness of the cellular layer 161 in the transparent foam film is less than the Shore hardness of the cellular layer 161 in the non-transparent foam film at 23°C, the storage modulus of the cellular layer 161 in the transparent foam film at 23°C is less than the storage modulus of the cellular layer 161 in the non-transparent foam film at 23°C, the light transmittance of the transparent foam film is greater than the light transmittance of the non-transparent foam film, and the reflectivity of the transparent foam film is less than the reflectivity of the non-transparent foam film. In this application, there are certain differences in the performance of the transparent foam film and the non-transparent foam film. The foam film 16 is divided into a transparent foam film and a non-transparent foam film according to the different amounts of fillers used in the cellular layer composition. In order to allow light to pass through, the amount of filler added to the transparent foam film is relatively small, while in order to block or reflect light, the amount of filler added to the non-transparent foam film is relatively large. The greater the amount of filler used in the cellular layer 161 of the foam film 16, the greater the Shore hardness and storage modulus of the cellular layer 161 at 23°C, the greater the reflectivity of the cellular layer 161 and the lower the transmittance. The cellular layer 161 in the transparent foam film has a low filler content, a low Shore hardness and storage modulus, high flexibility, and can play a good buffering role for instantaneous pressure. It also has a high transmittance, ensuring the amount of light transmitted. The cellular layer 161 in the non-transparent foam film has a high filler content, and has a greater Shore hardness and storage modulus than the cellular layer 161 of the transparent foam film. The cellular layer 161 of the non-transparent foam film has a high reflectivity, can reflect more light, and improve the light utilization rate of the single-sided component.

[0050] As an implementation method, when the adhesive layer is made of a transparent foam film, the adhesive layer is a transparent adhesive layer, and when the adhesive layer is made of a non-transparent foam film, the adhesive layer is a non-transparent adhesive layer. In the transparent adhesive layer, the pore size of the closed pores is 1-10 μm, and the volume resistivity is greater than or equal to 10 16 Ω·m; the density of the transparent adhesive layer is less than the density of the matrix resin, the Shore hardness of the transparent adhesive layer is less than or equal to 65HA, and the storage modulus of the transparent adhesive layer at 23°C is less than or equal to 6MPa. In the non-transparent adhesive layer, the pore size of the closed pore is 5-20μm, and the volume resistivity is greater than or equal to 10 14Ω·m; the Shore hardness of the non-transparent adhesive layer is less than or equal to 70HA, and the storage modulus of the non-transparent adhesive layer at 23°C is less than or equal to 13MPa. During the lamination process of the photovoltaic module 100, a part of the pores 161a in the foam film 16 disappears due to the resin filling effect under the action of heat and pressure, and the number of closed pores 121 in the adhesive layer after lamination is reduced accordingly, and the buffering performance will be reduced, but a part of the closed pores 121 are still preserved, and the photovoltaic module 100 can still provide good impact resistance and optical properties. The number of closed pores 121 in the adhesive layer obtained after lamination of the foam film 16 is less than the number of pores 161a in the foam film 16. However, due to the micro-cross-linking treatment, a certain proportion of closed pores 121 can still be retained in the adhesive layer. The foam film 16 can have a good protective effect on the battery cell 13 when the photovoltaic module 100 is packaged, and an excellent adhesive layer is obtained after the photovoltaic module 100 is packaged, which improves the power generation efficiency of the photovoltaic module 100 and extends its service life.

[0051] As an implementation method, when the porosity of the non-transparent adhesive layer is less than or equal to 6%, the density of the non-transparent adhesive layer is greater than the density of the matrix resin; when the porosity of the non-transparent adhesive layer is greater than 6%, the density of the non-transparent adhesive layer is less than the density of the matrix resin. The density of the non-transparent adhesive layer is less than the density of the matrix resin. In the non-transparent adhesive layer in the embodiment of the present application, since it contains more fillers and has closed cells different from conventional transparent adhesive films, its density is affected by the amount of filler added and the closed cell density. There is a case where the density is greater than the density of the matrix resin, and there is also a case where the density is slightly less than the density of the matrix resin.

[0052] As an implementation method, the density of the transparent adhesive layer is less than that of the non-transparent adhesive layer, the Shore hardness of the transparent adhesive layer is less than that of the non-transparent adhesive layer, the storage modulus of the transparent adhesive layer at 23°C is less than that of the non-transparent adhesive layer at 23°C, the light transmittance of the transparent adhesive layer is greater than that of the non-transparent adhesive layer, and the reflectivity of the transparent adhesive layer is less than that of the non-transparent adhesive layer. The transparent adhesive layer and the non-transparent adhesive layer are respectively obtained by laminating a transparent encapsulating film and a non-transparent encapsulating film during the component preparation process, so the performance of the transparent adhesive layer is correspondingly affected by the transparent foaming film, and the performance of the non-transparent adhesive layer is correspondingly affected by the non-transparent foaming film.

[0053] As an implementation method, the photovoltaic module 100 is made by stacking the front substrate 11, the foam film 16, the battery cell 13, the foam film 16 and the back substrate 15 in sequence and laminating them at 90°C-200°C. The packaging temperature of the photovoltaic module 100 is related to the packaging film raw material, and it is necessary to ensure that the packaging film is quickly cured at the lamination temperature. In the embodiment of the present application, the density of the closed cells 121 of the adhesive layer after lamination of the photovoltaic module 100 must also be considered. In order to ensure that the first adhesive layer 12 and the second adhesive layer 14 have an appropriate density of closed cells 121 after lamination, the lamination temperature range of the photovoltaic module 100 provided in the embodiment of the present application should be appropriately adjusted according to the foaming process design and the adhesive film raw material.

[0054] As an implementation method, the thickness of the cell 13 is 160 microns. In the embodiment of the present application, the photovoltaic module 100 can effectively relieve the instantaneous pressure when encapsulating, so it has a good protective effect on the cell 13. When the cell 13 is selected, thinner cells 13 can be used for lamination, which can effectively improve the power generation efficiency of the photovoltaic module 100 and reduce the cost of the cell 13.

[0055] In order to better understand the above technical solution, the above technical solution will be described in detail in combination with specific implementation methods. In the following examples and comparative examples, the density of the EVA resin used in the matrix resin is 0.948 g / cm 3 , the density of POE resin is 0.88g / cm 3 , the density of EPDM resin is 0.955g / cm 3 .

[0056] Example 1

[0057] like Figure 1 The photovoltaic module 100 shown is composed of a front substrate 11, a first adhesive layer 12, a cell 13, a second adhesive layer 14 and a back substrate 15, wherein the first adhesive layer 12 includes closed pores 121. The thickness of the cell 13 is 160 microns, and the lamination temperature of the photovoltaic module 100 is 150°C.

[0058] The first adhesive layer 12 is made of Figure 4The foam film 16 shown is made, and the foam film 16 is specifically a transparent foam film; the foam film 16 is only composed of a cellular layer 161; the cellular layer 161 is made of the following components in parts by weight: 100 parts of EVA resin, supercritical CO2 0.001 parts, crosslinking agent (diisopropylbenzene peroxide) 0.5 parts, auxiliary crosslinking agent (triallyl isocyanurate) 0.5 parts, heat stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) 0.1 parts, light stabilizer (poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}) 0.1 parts, ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 parts, magnesium hydroxide 0.1 parts.

[0059] The second adhesive layer 14 is made of Figure 5 The conventional adhesive film 21 shown is prepared, and the conventional adhesive film 21 is specifically a white adhesive film; the conventional adhesive film 21 is prepared by foaming the following components in parts by weight: 100 parts of EVA resin, 0.5 parts of a cross-linking agent (diisopropyl peroxide), 0.5 parts of a co-cross-linking agent (triallyl isocyanurate), 0.1 parts of a heat stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), and 0.1 parts of a light stabilizer (poly{[6-[( 0.1 parts of 1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}), 0.1 parts of ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol), and 10 parts of titanium dioxide.

[0060] Example 2

[0061] like Figure 2 The photovoltaic module 100 shown is composed of a front substrate 11, a first adhesive layer 12, a cell 13, a second adhesive layer 14 and a back substrate 15, wherein the second adhesive layer 14 includes closed pores 121. The thickness of the cell 13 is 160 microns, and the lamination temperature of the photovoltaic module 100 is 150°C.

[0062] The first adhesive layer 12 is made of Figure 5The conventional adhesive film 21 shown is made, and the conventional adhesive film 21 is specifically a transparent adhesive film; the conventional adhesive film 21 is made of the following components in parts by weight: 100 parts of EVA resin, 0.5 parts of a cross-linking agent (diisopropyl peroxide), 0.5 parts of a co-cross-linking agent (triallyl isocyanurate), 0.1 parts of a heat stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), 0.1 parts of a light stabilizer (poly{[6-[(1, 0.1 parts of 1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}), 0.1 parts of ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol), and 0.1 parts of magnesium hydroxide.

[0063] The second adhesive layer 14 is made of Figure 4 The foam film 16 shown is made, and the foam film 16 is specifically a white foam film; the foam film 16 is composed of only a cellular layer 161; the cellular layer 161 is foamed by the following components in parts by weight: 100 parts of EVA resin, 2 parts of microsphere foaming agent, 0.5 parts of cross-linking agent (diisopropyl peroxide), 0.5 parts of auxiliary cross-linking agent (triallyl isocyanurate), and 0.1 parts of thermal stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) , light stabilizer (poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}) 0.1 parts, ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 parts, titanium dioxide 10 parts.

[0064] Example 3

[0065] like Figure 3 The photovoltaic module 100 shown is composed of a front substrate 11, a first adhesive layer 12, a cell 13, a second adhesive layer 14 and a back substrate 15, wherein the first adhesive layer 12 and the second adhesive layer 14 both include closed pores 121. The thickness of the cell 13 is 160 microns, and the temperature during lamination of the photovoltaic module 100 is 150°C.

[0066] The first adhesive layer 12 is made of Figure 4The foam film 16 shown is made, and the foam film 16 is specifically a transparent foam film; the foam film 16 is only composed of a cellular layer 161; the cellular layer 161 is foamed by the following components in parts by weight: 100 parts of EVA resin, supercritical CO2 0.001 parts, crosslinking agent (diisopropylbenzene peroxide) 0.5 parts, auxiliary crosslinking agent (triallyl isocyanurate) 0.5 parts, heat stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) 0.1 parts, light stabilizer (poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}) 0.1 parts, ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 parts, magnesium hydroxide 0.1 parts.

[0067] The second adhesive layer 14 is made of Figure 4 The foam film 16 shown is made, and the foam film 16 is specifically a white foam film; the foam film 16 is only composed of a cellular layer 161; the cellular layer 161 is foamed by the following components in parts by weight: 100 parts of EVA resin, 2 parts of microsphere foaming agent, 0.5 parts of cross-linking agent (diisopropyl peroxide), 0.5 parts of auxiliary cross-linking agent (triallyl isocyanurate), and 0.1 parts of thermal stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) , light stabilizer (poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}) 0.1 parts, ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 parts, titanium dioxide 10 parts.

[0068] Example 4

[0069] like Figure 3 The photovoltaic module 100 shown is composed of a front substrate 11, a first adhesive layer 12, a cell 13, a second adhesive layer 14 and a back substrate 15, wherein the first adhesive layer 12 and the second adhesive layer 14 both include closed pores 121. The thickness of the cell 13 is 160 microns, and the lamination temperature of the photovoltaic module 100 is 150°C.

[0070] The first adhesive layer 12 is made of Figure 4The foam film 16 shown is made, and the foam film 16 is specifically a transparent foam film; the foam film 16 is only composed of a cellular layer 161; the cellular layer 161 is foamed by the following components in parts by weight: 100 parts of EVA resin, supercritical CO2 0.2 parts, crosslinking agent (diisopropyl peroxide) 0.5 parts, auxiliary crosslinking agent (triallyl isocyanurate) 0.5 parts, heat stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) 0.1 parts, light stabilizer (poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}) 0.1 parts, ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 parts, white carbon black 0.1 parts.

[0071] The second adhesive layer 14 is made of Figure 4 The foam film 16 shown is made, and the foam film 16 is specifically a transparent foam film; the foam film 16 is composed of only a cellular layer 161; the cellular layer 161 is made by foaming the following components in parts by weight: 100 parts of EVA resin, supercritical N2 0.2 parts, crosslinking agent (diisopropylbenzene peroxide) 0.5 parts, auxiliary crosslinking agent (triallyl isocyanurate) 0.5 parts, heat stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) 0.1 parts, light stabilizer (poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}) 0.1 parts, ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 parts, titanium dioxide 0.1 parts.

[0072] Example 5

[0073] like Figure 3 The photovoltaic module 100 shown is composed of a front substrate 11, a first adhesive layer 12, a cell 13, a second adhesive layer 14 and a back substrate 15, wherein the first adhesive layer 12 and the second adhesive layer 14 both include closed pores 121. The thickness of the cell 13 is 160 microns, and the lamination temperature of the photovoltaic module 100 is 160°C.

[0074] The first adhesive layer 12 is made of Figure 4The foam film 16 shown is made, and the foam film 16 is specifically a transparent foam film; the foam film 16 is composed of only a cellular layer 161; the cellular layer 161 is foamed by the following components in parts by weight: 100 parts of POE resin, 0.2 parts of foaming agent TSH, 0.5 parts of cross-linking agent (diisopropyl peroxide), 0.5 parts of auxiliary cross-linking agent (triallyl isocyanurate), 0.1 parts of heat stabilizer (tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester), 0.1 parts of light stabilizer (poly{[6-[(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl -piperidinyl)imino]-1,6-hexanediol [(2,2,6,6-tetramethyl-4-piperidinyl)imino]}) 0.1 part, UV absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 part, white carbon black 0.1 part; the transparent foam film is prepared and then subjected to ultraviolet light curing and micro-cross-linking treatment; during lamination, the cellular layer 161 is in close contact with the battery cell 13.

[0075] The second adhesive layer 14 is made of Figure 4 The foam film 16 shown is made, and the foam film 16 is specifically a white foam film; the foam film 16 is composed of only a cellular layer 161; the cellular layer 161 is foamed by the following components in parts by weight: 100 parts of EPDM resin, and a foaming agent OBSH 0.2 parts, crosslinking agent (diisopropylbenzene peroxide) 0.5 parts, auxiliary crosslinking agent (triallyl isocyanurate) 0.5 parts, heat stabilizer (tetrakis [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester) 0.1 parts, light stabilizer (poly {[6-[(1,1,3,3-tetramethylbutyl) amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl) imino]-1,6-hexanediol [(2,2,6,6-tetramethyl-4-piperidinyl) imino]}) 0.1 parts, ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 parts, titanium dioxide 10 parts; the white foam film is prepared and then subjected to heat curing and micro-crosslinking treatment.

[0076] Example 6

[0077] like Figure 3 A photovoltaic module 100 is shown, which is composed of a front substrate 11, a first adhesive layer 12, a cell 13, a second adhesive layer 14 and a back substrate 15, wherein the first adhesive layer 12 and the second adhesive layer 14 both include closed pores 121. The thickness of the cell 13 is 160 microns, and the lamination temperature of the photovoltaic module 100 is 100°C.

[0078] The first adhesive layer 12 is made of Figure 4The foam film 16 shown is made, and the foam film 16 is specifically a transparent foam film; the foam film 16 is composed of only a cellular layer 161; the cellular layer 161 is foamed by the following components in parts by weight: 100 parts of PU resin, 0.2 parts of ammonium bicarbonate, 0.5 parts of a cross-linking agent (diisopropyl peroxide), 0.5 parts of a co-cross-linking agent (triallyl isocyanurate), 0.1 parts of a heat stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), and 0.1 parts of a light stabilizer (poly{[6- [(1,1,3,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}) 0.1 part, ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 part, magnesium oxide 0.1 part; the transparent foam film is prepared and then subjected to radiation curing and micro-crosslinking treatment.

[0079] The second adhesive layer 14 is made of Figure 4 The foam film 16 shown is made, and the foam film 16 is specifically a white foam film; the foam film 16 is composed of only a cellular layer 161; the cellular layer 161 is foamed by the following components in parts by weight: 100 parts of POE resin, and a foaming agent AC 0.2 parts, crosslinking agent (diisopropyl peroxide) 0.5 parts, auxiliary crosslinking agent (triallyl isocyanurate) 0.5 parts, heat stabilizer (tetrakis [β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester) 0.1 parts, light stabilizer (poly { [6- [(1,1,3,3-tetramethylbutyl) amino]]-1,3,5-triazine-2,4- [(2,2,6,6,-tetramethyl-piperidinyl) imino] -1,6-hexanediol [(2,2,6,6-tetramethyl-4-piperidinyl) imino]}) 0.1 parts, ultraviolet absorber (2- (4,6-diphenyl-1,3,5-triazine-2-yl) -5-hexyloxy-phenol) 0.1 parts, talc 10 parts; the white foam film is prepared and then subjected to microwave curing and micro-crosslinking treatment.

[0080] Comparative Example 1

[0081] like Figure 6 As shown, a conventional photovoltaic module 200 is composed of a front substrate 11, a first adhesive layer 12, a battery cell 13, a second adhesive layer 14 and a back substrate 15; the thickness of the battery cell 13 is 160 microns, and the lamination temperature of the photovoltaic module 100 is 150°C. The first adhesive layer 12 is composed of Figure 5The conventional adhesive film 21 shown is made, which is a transparent packaging adhesive film, which is made of the following components in parts by weight: 100 parts of EVA resin, 0.5 parts of cross-linking agent (diisopropyl peroxide), 0.5 parts of auxiliary cross-linking agent (triallyl isocyanurate), 0.1 parts of heat stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), and 0.1 parts of light stabilizer (poly{[6-[(1,1,3, 3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}) 0.1 part, ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 part, magnesium hydroxide 0.1 part. The second adhesive layer 14 is made of Figure 5 The conventional adhesive film 21 shown is made, which is a white encapsulation adhesive film, which is made of the following components in parts by weight: 100 parts of EVA resin, 0.5 parts of a cross-linking agent (diisopropyl peroxide), 0.5 parts of a co-cross-linking agent (triallyl isocyanurate), 0.1 parts of a heat stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), and 0.1 parts of a light stabilizer (poly{[6-[(1,1,3 ,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}) 0.1 parts, ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 parts, titanium dioxide 10 parts.

[0082] Comparative Example 2

[0083] like Figure 6 As shown, a conventional photovoltaic module 200 is composed of a front substrate 11, a first adhesive layer 12, a battery cell 13, a second adhesive layer 14 and a back substrate 15; the thickness of the battery cell 13 is 160 microns, and the lamination temperature of the photovoltaic module 100 is 150°C. The first adhesive layer 12 and the second adhesive layer 14 are made of Figure 5The conventional adhesive film 21 shown is made, which is a transparent packaging adhesive film, which is made of the following components in parts by weight: 100 parts of EVA resin, 0.5 parts of cross-linking agent (diisopropyl peroxide), 0.5 parts of auxiliary cross-linking agent (triallyl isocyanurate), 0.1 parts of heat stabilizer (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), and 0.1 parts of light stabilizer (poly{[6-[(1,1,3 ,3-tetramethylbutyl)amino]]-1,3,5-triazine-2,4-[(2,2,6,6,-tetramethyl-piperidinyl)imino]-1,6-hexanediol[(2,2,6,6-tetramethyl-4-piperidinyl)imino]}) 0.1 parts, ultraviolet absorber (2-(4,6-diphenyl-1,3,5-triazine-2-yl)-5-hexyloxy-phenol) 0.1 parts, and white carbon black 0.1 parts.

[0084] Performance Test:

[0085] 1. The density, Shore hardness, storage modulus at 23°C, pore density, pore diameter and volume resistivity of the cellular layer in Examples 1-6, and the density, Shore hardness, storage modulus at 23°C, pore density, pore diameter and volume resistivity of the film in Comparative Examples 1-2 were tested respectively;

[0086] 2. The power generation efficiency, impact resistance, packaging qualification rate and water vapor transmission rate of the photovoltaic modules in Examples 1-6 and Comparative Examples 1-2 were tested respectively; the power generation efficiency was tested using a solar module tester.

[0087] Performance test results:

[0088] 1. Table 1 below shows the relevant performance test results of the cellular layer in Examples 1-6 and Comparative Examples 1-2;

[0089] Table 1 Test results of the performance of the cellular layer of Examples 1-6 and Comparative Examples 1-2

[0090]

[0091] It can be seen from Table 1 above that in Examples 1-6 of the present application, at least a portion of the packaging film (specifically the foaming layer therein) is obtained by foaming and has cells of a certain pore size.

[0092] 2. Table 2 below shows the relevant performance test results of the first adhesive layer and the second adhesive layer in Examples 1-6 and Comparative Examples 1-2;

[0093] Table 2 Performance test results of the first adhesive layer and the second adhesive layer of Examples 1-6 and Comparative Examples 1-2

[0094]

[0095]

[0096] As can be seen from Table 2 above, in Examples 1-6 of the present application, at least part of the adhesive layer is made of a foamed film, and a portion of closed-cell pores are still retained despite the lamination process. Compared with the adhesive layer without closed cells made by conventional packaging films, the adhesive layers in Examples 1-6 have lower density, lower Shore hardness, relatively small storage modulus, and significantly improved volume resistivity when the same film system is used. At the same time, due to the presence of closed cells in some adhesive layers, their light transmittance and reflectivity are also improved to a certain extent. The first adhesive layer of Example 1-6 has a higher light transmittance, and the second adhesive layer of Example 1-6 has a higher reflectivity. It can be seen that the foamed layer obtained by foaming has better light transmittance in the transparent packaging film, and has better reflectivity in the white film by interacting with the filler.

[0097] 3. Table 3 below shows the relevant performance test results of the photovoltaic modules in Examples 1-6 and Comparative Examples 1-2;

[0098] Table 3 Photovoltaic module performance test results of Examples 1-6 and Comparative Examples 1-2

[0099]

[0100] It can be seen from Table 3 above that since at least part of the adhesive layer is made of foamed adhesive film, the photovoltaic modules in Examples 1 to 6 of the present application have better lamination qualification rate and module power generation efficiency.

[0101] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A photovoltaic module, comprising, in sequence, a front substrate, an adhesive layer, a cell, an adhesive layer and a back substrate, characterized in that: At least one of the adhesive layers is selected from a foamed adhesive film that has been micro-crosslinked and has closed pores, wherein the closed pores do not protrude from the surface of the adhesive layer; the pore size of the closed pores is 0.5-20 μm; and the porosity of the adhesive layer is 0.5-40%; The foam film comprises a cellular layer having pores, the raw materials of the cellular layer comprise a base resin, a foaming agent, a functional auxiliary agent and a filler, the foaming agent comprises at least one of a physical foaming agent or a chemical foaming agent, the base resin comprises at least one of an EVA resin, a POE resin, a PE resin, a PVB resin, an EPDM resin or a PU resin, the physical foaming agent comprises at least one of CO2, N2 or a microsphere foaming agent, and the chemical foaming agent comprises at least one of a foaming agent TSH, a foaming agent OBSH, a foaming agent AC, ammonium bicarbonate, sodium bicarbonate, potassium bicarbonate, calcium bicarbonate or magnesium bicarbonate; In the cellular layer of the foam film, the Shore hardness of the cellular layer is less than or equal to 75HA, the storage modulus of the cellular layer at 23°C is less than or equal to 15MPa, the porosity is 1-20%, the pore diameter is 1-40μm, and the volume resistivity is greater than or equal to 10 14 Ω·m.

2. The photovoltaic module according to claim 1, characterized in that: The pore diameter of the closed pores is 0.5 to 10 μm.

3. The photovoltaic module according to claim 1, characterized in that: The porosity of the bonding layer is 1-10%.

4. A photovoltaic module according to claim 1, characterized in that: The Shore hardness of the bonding layer is less than or equal to 75HA, the storage modulus of the bonding layer at 23°C is less than or equal to 15MPa, and the volume resistivity of the bonding layer is greater than or equal to 10 14 Ω·m.

5. A photovoltaic module according to claim 1, characterized in that: The bonding layer includes a transparent bonding layer and a non-transparent bonding layer, and the raw material of the bonding layer includes a base resin; The adhesive layer arranged between the front substrate and the battery cell is the first adhesive layer, and the adhesive layer arranged between the back substrate and the battery cell is the second adhesive layer; the first adhesive layer is the transparent adhesive layer, and the second adhesive layer is the transparent adhesive layer or the non-transparent adhesive layer.

6. A photovoltaic module according to claim 5, characterized in that: In the transparent adhesive layer, the pore size of the closed pores is 1-10 μm, and the volume resistivity is greater than or equal to 10 16 Ω·m; the density of the transparent adhesive layer is less than the density of the matrix resin, the Shore hardness of the transparent adhesive layer is less than or equal to 65HA, and the storage modulus of the transparent adhesive layer at 23° C. is less than or equal to 6MPa.

7. A photovoltaic module according to claim 5, characterized in that: In the non-transparent adhesive layer, the pore size of the closed pores is 5-20 μm, and the volume resistivity is greater than or equal to 10 14 Ω·m; the Shore hardness of the non-transparent adhesive layer is less than or equal to 70HA, and the storage modulus of the non-transparent adhesive layer at 23° C. is less than or equal to 13MPa.

8. A photovoltaic module according to claim 7, characterized in that: When the porosity of the non-transparent adhesive layer is less than or equal to 6%, the density of the non-transparent adhesive layer is greater than the density of the matrix resin; when the porosity of the non-transparent adhesive layer is greater than 6%, the density of the non-transparent adhesive layer is less than the density of the matrix resin.

9. A photovoltaic module according to claim 5, characterized in that: The density of the transparent adhesive layer is lower than that of the non-transparent adhesive layer, the Shore hardness of the transparent adhesive layer is lower than that of the non-transparent adhesive layer, the storage modulus of the transparent adhesive layer at 23°C is lower than that of the non-transparent adhesive layer at 23°C, the transmittance of the transparent adhesive layer is higher than that of the non-transparent adhesive layer, and the reflectivity of the transparent adhesive layer is lower than that of the non-transparent adhesive layer.

10. A photovoltaic module according to claim 1, characterized in that: The micro-crosslinking treatment includes at least one of ultraviolet light curing micro-crosslinking, thermal curing micro-crosslinking, radiation curing micro-crosslinking or microwave curing micro-crosslinking.

11. A photovoltaic module according to claim 1, characterized in that: The functional auxiliary agent includes at least one of a crosslinking agent, a co-crosslinking agent, a coupling agent, a heat stabilizer, a light stabilizer or an ultraviolet absorber.

12. A photovoltaic module according to claim 1, characterized in that: The filler includes at least one of carbon black, titanium dioxide, barium sulfate, bentonite, white carbon, wollastonite, whisker silicon, talc, magnesium hydroxide, magnesium oxide, aluminum hydroxide or aluminum oxide.

Citation Information

Patent Citations

  • Adhesive membrane for packaging multi-layer structure photovoltaic module and preparation method of adhesive membrane

    CN107400471A

  • Packaging adhesive film and photovoltaic module

    CN214991264U